Factors of Adolescent Suicide - Donna Davis (EDIS)
“The loss of a child to suicide can be particularly devastating to parents, friends, and others in the child’s life. When my daughter came home one day telling me of a classmate who was contemplating suicide, the flood of fear for her friend and for the fact that my daughter was so closely exposed to such pain was one of those life-stopping moments.” This 2-page Family Album Radio transcript was written by Donna Davis and published by the UF Department of Family, Youth and Community Sciences, August 2012.